(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2020)
Recently, scratch technique is widely used for characterizing the mechanical properties of awide range of surfaces. In the engineering applications and in order to determine the relativehardness of materials, coatings and paints evaluations, and appraisal a variety of materialdamage countenance when subjected to asperity of the hard counterface, a scratch test wassuccessfully used. In the current work, we have reviewed theoretical models that have beendeveloped in the field of scratching and the scratch way that used for characterizationpolymeric surfaces. In order to design scratch-resistant polymers, we also discussed thevarious wear and scratch damage mechanisms for polymer and its composites. In addition,we discussed the influence of types and concentration of filler on the wear and scratchresistance. The aim of this work is to review the theoretical models that have been developedin the field of scratching and the scratch way that used for characterization polymeric surfaces.